(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
The article discusses the problem of determining the basic functions of metaphor analysis in pedagogical discourse from the point of view of the conceptual approach. The metaphor is considered to be not only as a means of communication, but a way of thinking, communicative behavior of participants in pedagogical discourse. It acts not only as a unit of training, but also a condition for the formation of reflexive competence. The problem of this study is to define the basic functions of metaphorical analysis in pedagogical discourse that helps to identify the nature and orientation of upbringing and education, the style of organization of the pedagogical process, and the content of instruction. The formation of the culture of metaphor analysis is a condition for the development of reflexive competence of both teachers and students. The purpose of this study is to determine the functions of metaphor in pedagogical discourse, taking into account the meaningful and functional characteristics of pedagogical and didactic metaphors. Novelty. It defines the basic functions of metaphor analysis in the pedagogical discourse, taking into account the pecularities of the pedagogical discourse, its dialogical and interactive nature, the appropriateness of using the constructive, fasilitational teaching technologies and pedagogical, linguistic conditions for the formation of students’ reflexive competence.